Study on Hydrodynamic Characteristics of Continuous Distribution Vegetation Patches Based on LES - GAO Huan; GONG Yiqing; MAO Jinqiao; CHEN Yanhong; DAI Jie; WANG Kang; MENG Dinghua; YANG Ji (工程科学与技术)
There are numerous continuous plant patches in rivers and lakes, and the distance between these patches and the riverbank changes with water level fluctuations, affecting the flow field structure. This study uses the Hydro 3D open-source code and LES technology based on the Immersed Boundary method to construct a mathematical model of circular rigid emergent vegetation patches to clarify the hydrodynamic characteristics of continuous plant patches under varying water levels. The accuracy of the mathematical model is verified using experimental data, and three-dimensional hydrodynamic characteristics are then analyzed. The results show that a “sheltering effect” exists between continuous plant patches, a “low-speed zone” appears behind the patch, and lateral outflow is generated when water flows toward both sides. Individual plants within the patch do not exhibit significant group effects. High turbulence energy occurs on both sides of the patch due to shear, and the presence of downstream patches disrupts the vortex structure behind the upstream patches. When the solid volume fraction Φ inside a patch is 0.17, the downstream flow forms a vortex structure, which facilitates nutrient enrichment downstream of the patch. The distance (S) between the plant patch and the wall significantly affects the flow field structure around the patch. As S decreases, the flow velocity near the bank decreases, weakening the erosion of the riverbank by the water flow, and the strength and integrity of the vortex structure around and within the continuous plant patches gradually decrease. When Φ decreases from 0.17 to 0.05, the sheltering effect of the upstream patch weakens, and a vortex “blank zone” with a length of approximately 1D appears behind the patch, preventing the formation of a stable vortex structure at the patch scale; only a small amount of vortex exists at the plant scale. The research results provide a reference for clarifying the hydrodynamic characteristics around plant patches during water level fluctuations in rivers and lakes.